Day 3 Wed, October 23, 2019 2019
DOI: 10.2118/198610-ms
|View full text |Cite
|
Sign up to set email alerts
|

Digital Rock Technology Accelerates Carbonate Rock Laboratory Analysis

Abstract: This paper describe an application of combined experimental and digital technology workflow for field appraisal. It includes the description of heterogeneous low permeability X oil field located in the southeastern part of the Kurdistan Region of Iraq and its field development planning (FDP) challenges. An integrated laboratory study of low permeability carbonate reservoir rocks (dolomitic limestones) included a digital rock (DR) workflow that accelerated the time to complete core analysis progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In previous publications it has been demonstrated that various multiphase compositional problems can be modeled in the frame of the density functional hydrodynamics (DFH) [7][8][9][10][11][12][13][14][15][16][17], including practical digital rock applications [18][19][20][21][22][23][24][25][26]. In the present work we discuss the pore-scale modeling of gas-condensate mixtures in digital rock models obtained by X-ray microCT.…”
Section: Introductionmentioning
confidence: 99%
“…In previous publications it has been demonstrated that various multiphase compositional problems can be modeled in the frame of the density functional hydrodynamics (DFH) [7][8][9][10][11][12][13][14][15][16][17], including practical digital rock applications [18][19][20][21][22][23][24][25][26]. In the present work we discuss the pore-scale modeling of gas-condensate mixtures in digital rock models obtained by X-ray microCT.…”
Section: Introductionmentioning
confidence: 99%
“…In the oil and gas industry, a precise digital twin of a sample is one of the cornerstones of Digital Rock workflow [8,9], which enables mathematical simulations of fluids flow in porous media, and estimations of the numerous physical and chemical characteristics of oil-bearing rocks. The advanced Digital Rock methodology consists of simulation on various scales including the nanoscale [10,11]. different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Production-driven rock types have poor links with geological and petrophysical data because of the different scale of measurements. For example, core porosity and permeability are obtained from 30 mm core plugs, log vertical resolution is about 0.1-1 m, and production logging and well tests are used to analyze larger intervals, 10 m and higher [13,25,26].…”
mentioning
confidence: 99%